Endogenous transport costs in international trade - Jörn Kleinert; Julia Spies (Institut für Angewandte Wirtschaftsforschung (IAW), 2011)
In this paper we claim that distance alone is a poor proxy for international transport costs in empirical studies. We model a manufacturing and a transport sector and let the level of manufacturing exports determine the demand for transport services. Above a particular trade level, transport service suppliers find it profit-maximizing to invest in an advanced transport technology, which lowers their marginal costs and as a consequence, equilibrium transport prices. Transport costs thus vary with two characteristics: with the distance between two locations and with the endogenous decision to invest in a more efficient technology which is driven, in turn, by the bilateral export level. A simulation exercise reveals that ignoring the effect of the investment decision on transport costs biases empirical results. The empirical estimations rely on newly collected transport price data from United Parcel Service (UPS). We apply an instrumental variable (IV) estimator to account for the endogeneity of the investment decision. Our results confirm that transport prices are influenced by both the distance and the level of exports between two countries. We find that trade partners with 10% more exports enjoy 0.8% lower transport prices.
Keywords: F12; F15; R41; 330; Distance; endogenous transport costs; Transportkosten; Außenwirtschaft; Exportindustrie; Verkehrsgewerbe; Investition; Wirtschaftliche Effizienz; Verkehrstarif; Theorie; Schätzung; OECD-Staaten